A coupled thermo–hydro-mechanical–chemical model for underground cemented tailings backfill. (August 2015) - Cui, Liang; Fall, Mamadou
Highlights: A fully coupled thermo–hydro-mechanical–chemical (THMC) model for cemented tailings backfill. The model validation results confirm the prediction capability of the THMC model. The developed model can be utilized as an effective tool to perform the optimal design of CPB. Abstract: Cemented paste backfill (CPB), a mixture of tailings, water and binder, is extensively used in underground mines worldwide for ground support and tailings disposal. The prediction of the behavior of CPB structures from early to advanced ages is of great practical importance. Once placed underground, the behavior of CPB is controlled by complex multiphysics (thermal, hydraulic, chemical and mechanical) processes. Modeling of the coupled THMC processes that occur in CPB are crucial for reliably assessing and predicting the performance of CPB structures. Yet there is currently no tool to predict the thermo–hydro-mechanical–chemical (THMC) behavior of CPB, or the performance of CPB under coupled THMC loadings. Therefore, a new multiphysics model is presented in this paper to describe and predict the coupled THMC behavior of CPB and its evolution with time. The governing equations of the model result from a combination of a set of conservation and constitutive equations. Four balance equations (water and air mass, momentum (mechanical equilibrium) and energy conservation equations) are taken into consideration. The model considers full coupling between the thermal, hydraulic, chemical (binder hydration) processes and CPB deformation as well as changes in CPB properties resultant of these phenomena, such as stress–strain relationship, thermal conductivity, permeability, porosity, and strength. The model coefficients are identified in terms of measurable parameters. The prediction capability of the developed model is then tested against laboratory and field tests conducted on CPB. Good agreement between the modeling results and experimental data confirms the capability of the developed model to well capture the THMC behavior of CPB and its evolution.